A mononuclear iron(iii) complex with unusual changes of color and magneto-structural properties with temperature: synthesis, structure, magnetization, multi-frequency ESR and DFT study. Issue 6 (19th January 2022) - Garg, Nitish Kumar; Goriya, Yogesh; Manojveer, Seetharaman; Muratović, Senada; Pajić, Damir; Cetina, Mario; Petreska, Irina; Krupskaya, Yulia; Kataev, Vladislav; Johnson, Magnus T.; Wendt, Ola F.; Žilić, Dijana
Abstract : A new mononuclear iron(iii ) complex with a high-spin magnetic state S = 5/2 shows an unusual change in ESR spectra with temperature and non-spin-crossover driven thermochromism. Abstract : From the reaction of 2-hydroxy-6-methylpyridine (L) with iron(ii ) tetrafluoroborate, a new mononuclear iron(iii ) octahedral complex [FeL6 ](BF4 )3 has been isolated. The color of the complex reversibly changed from red at room temperature to yellow-orange at the liquid nitrogen temperature. Magnetization measurements indicate that iron(iii ) in [FeL6 ](BF4 )3 is in a high-spin state S = 5/2, from room temperature to 1.8 K. The high-spin ground state of iron(iii ) is also confirmed by DFT calculations. Although the spin-crossover of the complex is not observed, X-band and multifrequency high-field/high-frequency electron spin resonance (ESR) spectroscopy shows rather uncommon iron(iii ) spectra at room temperature and an unusual change with cooling. Spectral simulations reveal that the S = 5/2 ground state multiplet of the complex can be characterized by the temperature independent axial zero-field splitting parameter of | D | = +2 GHz (0.067 cm −1 ) while the value of the rhombic parameter E of the order of some tenths MHz increases on lowering the temperature. Single crystal X-ray diffraction (SCXRD) shows that the iron(iii ) coordination geometry does not change with temperature while supramolecular interactions are temperature dependent, influencing the iron(iii ) rhombicity. Additionally, the DFT calculations show temperature variation of the HOMO–LUMO gap, in agreement with the changes of color and ESR-spectra of the iron(iii ) complex with temperature.